PORTUGUESE AS A HOST LANGUAGE FOR SENEGALESE MIGRANTS IN RIO GRANDE, RS, BRAZIL - Lúcia Lovato Leiria; Luciana Pilatti Telles; Adriano Luiz Ribeiro Freitas (Diacrítica, 2019)
Brazilian reputation as a land of opportunities has attracted immigrants searching for a better living. It is considerable the number of Senegalese in Rio Grande, RS, creating a demand for the teaching of Portuguese as a host language to immigrants. This paper results from reflections on a university extension project to promote the integration of these people in the local culture through Portuguese learning/ teaching. This project was also aimed at offering linguistic grounds for social interaction in Portuguese; providing contact with work-related text genres; and improving reading competences in texts addressing work and daily life. Thus, theoretical background from Interactional Sociolinguistics (Gumperz 1982) and Cultural Anthropology (Matta 2001) have been considered here. From the pedagogical point of view, this work was based upon the Task-based Approach (Janowska 2014; Willis 1996) has been chosen to solve specific needs of the group. In general, it was easy for the students to learn new words, but they showed some difficulties on the phonetic and phonological levels, such as distinguishing /z/ from /ʒ/; /s/ from /ʃ/; /l/ from /ʎ/. As to social impact, this project helped some students find formal jobs.